Pengaruh Leverage dan Ukuran Perusahaan terhadap Profitabilitas pada PT. Astra International TBK Periode 2015–2024 (Jurnal Ekonomi Bisnis dan Akuntansi, 2024)
This study aims to analyze the influence of leverage and company size on the profitability of PT Astra International Tbk in the 2015–2024 period and examine the capital structure on the company value of PT Indofood Sukses Makmur Tbk in the 2020–2024 period. This study uses a quantitative approach with secondary data in the form of quarterly financial statements as many as 20 observations. The independent variables used are the size of the company and capital structure, while the dependent variable is the value of the company as measured by the price to book value (PBV). The analysis was carried out by multiple linear regression to test the partial or simultaneous influence of the two independent variables. The results show that the size of the company has a negative and significant effect on the value of the company, indicating that the increase in assets is not always followed by an increase in the market's perception of the value of the company. On the other hand, the capital structure does not have a significant effect on the company's value, so changes in the composition of debt to assets are not the main factor in determining Indofood's PBV. However, simultaneously the size of the company and the capital structure are proven to have a significant effect on the value of the company, confirming that the combination of the two remains an important consideration in market valuations. The implications of this study emphasize the importance of asset growth efficiency and prudence in funding policies to maintain the sustainability of company value.